A Retrospective Analysis Comparing Technical Difficulty and Safety between Right and Left-sided Percutaneous Transhepatic Biliary Drainage in a Nondilated Biliary System - Patel, Ranjan Kumar; Tripathy, Taraprasad; Pattnaik, Bramhadatta; Dutta, Tanmay; Gupta, Sunita; Nayak, Hemant Kumar; Panigrahi, Manas Kumar; Das, Deepak; Barik, Sandip Kumar; Mohakud, Sudipta; Naik, Suprava; Deep Bag, Nerbadyswari (Indian Journal of Radiology and Imaging, 2025)
Objective The aim of this study was to compare the technical difficulty and safety between right-sided percutaneous transhepatic biliary drainage (R-PTBD) and left-sided percutaneous transhepatic biliary drainage (L-PTBD) in patients with nondilated bile ducts.Materials and Methods Forty-two patients (22 males and 20 females with a mean age of 46.2 ± 13.7 years) who received PTBD in nondilated bile ducts (from September 2021 to January 2024) were dichotomized into the R-PTBD (n = 22) and L-PTBD (n = 20) groups. The number of needle punctures, successful biliary punctures, technical success, difficulty in catheter placement, total fluoroscopic time, total procedure time, overall complications, and hemorrhagic complications were evaluated and compared between the groups.Results The R-PTBD group had significantly fewer needle punctures for biliary access (3.9 ± 1.3 vs. 4.3 ± 1.3; p = 0.004) and a shorter procedure duration (21 ± 8.5 vs. 29.9 ± 13.2 minutes; p = 0.021) than the L-PTBD group. The successful biliary puncture (20 [90.9%] vs. 15 [75%]; p = 0.229) and technical success rate (20 [90.9%] vs. 14 [70%]; p = 0.123) were also higher for the R-PTBD group than for the L-PTBD group, while R-PTBD required less fluoroscopic time (5.83 [3.5–8.13] vs. 8.16 [4.34–12.9] minutes; p = 0.113). However, these differences did not reach statistical significance (p > 0.05). Further, difficulty during catheter placement was more frequently encountered in the L-PTBD group (02 [9%] vs. 04 [20%]; p = 0.367). The overall complication and hemorrhagic complication rates were comparable between both groups.Conclusion When both approaches are equally suitable for patients with nondilated bile ducts, R-PTBD may be favored over L-PTBD, given the evidence demonstrating less technical difficulty in the right-sided approach than in the left-sided approach.
Keywords: percutaneous transhepatic biliary drainage; nondilated bile ducts; right-sided versus left-sided PTBD; adverse events; benign biliary system; obstructive biliopathy